Whistleblowing as a new regulatory instrument in global governance: the case of tax evasion. Issue 6 (2nd November 2018) - Porter, Tony; Ronit, Karsten
Abstract: The cross-border impacts of whistleblowing recently have become far more visible and consequential, as evident with the 'Paradise' and 'Panama Papers' leaks, which exposed tax and other financial wrongdoings of prominent personalities around the world, leading to scandals, resignations and prosecutions. Despite its new prominence, whistleblowing often continues to be seen as a series of ad hoc chance acts. We argue instead that whistleblowing is an increasingly institutionalized regulatory tool that is enabled by an emergent 'whistleblowing system', with similarities to other new forms of informal global governance. Whistleblowing can be controversial, and we develop a framework for assessing whether any particular whistleblowing event and the system that enables it are in the public interest. We then apply this analysis to the case of global tax evasion. We conclude that a whistleblowing system can make important contributions to difficult cross-border regulatory challenges such as tax evasion, especially where other governance systems fail.